Forecasting the financial failure of Islamic banks using the Altman model, ---- springate model and ---- Sherrod model / an analytical study in Islamic banks listed on the Iraq Stock Exchange - Qader, Aso Bahaulddin (Journal of Economics and Administrative Sciences, 2020)
Profit is a goal sought by all banks because it brings them income and guarantees them survival and continuity, and on the other hand, facing commitments without financial crisis. Hence the idea of research in his quest to build scientific tools and means that can help bank management in particular, investors, lenders and others to predict financial failure and to detect early financial failures. The research has produced a number of conclusions, the most important of which is that all Islamic banks sample a safe case of financial failure under the Altman model, while according to the Springate model all Islamic banks sample a search for a financial failure except the Islamic Bank of Noor Iraq for Investment and Finance )BINI(. According to Sherrod's model, the placement of some Islamic banks in the search sample is financially sound, others have little chance of being exposed to the risks of bankruptcy. The research also provided scientific value to bank administrations through the establishment of a specialized administrative unit whose main work is to assess and diagnose risk and financial failure and ways to address them, as well as to report periodically on early financial failures.